Scientometric Profile of Biochemistry Research in India a Study Based on Web of Science - K.G., Sudhier; V, Dileepkumar (DESIDOC Journal of Library & Information Technology, 2020)
The paper examines 25,132 biochemistry research contributions of Indian scientists covered in the Web of Science for a period of 10 years (2004-2013). It was found that the biochemistry research is gradually growing and average annual growth rate was 36.84 per cent. The solo research was not prevalent and team research is more in the Indian biochemistry research and 97.46 per cent publications were contributed by multi- authors. It was observed that the value of co- authorship index was generally increasing and it varied from 93 to 105 during the period of study. Journal articles contribute 89.43 per cent of the total output followed by reviews (7.14 %). Indian researchers collaborate largely with the researchers of USA (2.49 %). The geographical distribution shows that Tamil Nadu, Uttar Pradesh and Delhi lead the list. The study shows that, C. Abdul Jaleel (58) and L. Pai (37) are the top ranked authors in the field. ‘Plos One’ is the top ranked journal and it published 296 papers during the study period. Academic institutions contribute more number of papers (50.26 %) followed by research institutions (28.24 %). The Lotka’s law was not found fit with the observed author productivity distribution of Indian biochemistry research.